The Influences of Carbon Composition on the Performance of Zn-Mn0.25Fe2.75O4@C Thin Films as Zinc-Ion Battery Electrodes - Mohammad Naim Bahar; Eny Latifah; Nadiya Miftachul Chusna; Kormil Saputra; Fadhil Fathurochman; Abdul Majeed Himat; Sunaryono Sunaryono (JPSE (Journal of Physical Science and Engineering), 2024)
Batteries based on Zinc-ion (ZIB) have a high capacity, low cost, low redox potential, and impressive electrochemical stability in water due to their hydrogen evolution. Fe3O4 NPs with carbon coated can significantly increase the electrical conductivity of battery. This study investigates the impact of carbon addition on the performance of Zn-Mn0.25Fe2.75O4@C as an electrode material for zinc-ion batteries. The research focuses on developing Zn-Mn0.25Fe2.75O4@C, which combines the advantages of zinc-ion batteries with the improved magnetic and electrical properties of magnetite materials. The material was synthesized using a spin coating method and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), vibrating sample magnetometry (VSM), transmission electron microscopy (TEM), cyclic voltammetry (CV), and charge-discharge (CD) tests. The addition of carbon was found to enhance specific capacitance, energy density, power density, cycle stability, and magnetic properties of the battery electrodes. FTIR characterization indicated the presence of O-H, C-O, Fe-O, Mn-O, C=C, C-N, and C=O groups. XRD revealed a cubic crystal structure with particle sizes between 6.10 nm and 11.53 nm. VSM analysis demonstrated a reduction in magnetization, coercivity, and magnetic remanence with carbon addition. TEM analysis showed an average particle size of 11.5 nm and aggregation of magnetite nanoparticles. CV results indicated the significant potential for Zn-Mn0.25Fe2.75O4@C as a battery electrode with the highest specific capacitance in MCF2. Charge-discharge tests highlighted that MCF2 is ideal for large energy storage, MCF3 for fast charging, and MCF4 for low-performance applications.